Epigenetic Mechanisms of the Cambrian Explosion - R Cabej, Nelson; R Cabej, Nelson (Academic Press, 2019)
Epigenetic Mechanisms of the Cambrian Explosion provides readers with a basic biological knowledge and epigenetic explanation of the biological puzzle of the Cambrian explosion, the unprecedented rapid diversification of animals that began 542 million years ago. During an evolutionarily instant of ~10 million years, which represents only 0.3% of the time of existence of life on Earth, or less than 2% of the time of existence of metazoans, all of the 30 extant body plans, major animal groups (phyla) and several extinct groups appeared. The work helps address this phenomena and tries to answer remaining questions for evolutionary biology, epigenetics, and scientific researchers. The book recognizes and presents objective representations of alternative theories for epigenetic evolution in this period, with the author drawing on his epigenetic theory of evolution to explain the causal basis of the Cambrian explosion. Both empirical evidence and theoretical arguments are presented in support of this thought-provoking epigenetic theory. - Explains the Cambrian explosion from an entirely epigenetic view - Takes a causal rather than descriptive approach to the phenomenon - Allows for a broad readership, including those with only a basic biological knowledge, while maintaining scientific rigor